INFERTILITY - Saraswati, Andini (Majority, 2015)
Abstract Infertility is the inability to contain up to deliver the baby alive after one year of regular sexual intercourse and do not use any contraception / after deciding to have children . Type of infertility is divided into two , namely primary infertility and secondary infertility . Many factors affect the incidence of both primary and secondary infertility in terms of men, women , and other factors . In terms of women problems in the cervix , tubes , ovaries , vagina , uterus and ovulation disorders . In terms of male factor problems such as coitus , ejaculation , employment and other factors may cause the incidence of infertility . Age and lifestyle factors are also not spared from the cause of secondary infertility . Consultation to the gynecologist is important for couples who do not have children after a minimum of one year of marriage. Keywords : ejaculation,infertility , ovulation, sexual Abstrak Infertilitas merupakan ketidakmampuan untuk mengandung sampai melahirkan bayi hidup setelah satu tahun melakukan hubungan seksual yang teratur dan tidak menggunakan alat kontrasepsi apapun/setelah memutuskan untuk mempunyai anak. Jenis infertilitas terbagi menjadi dua, yakni infertilitas primer dan infertilitas sekunder. Banyak faktor yang mempengaruhi kejadian infertilitas baik primer maupun sekunder dari segi pria, wanita, maupun faktor lain. Dari segi wanita masalah pada serviks, tuba, ovarium, vagina, uterus dan gangguan ovulasi. Dari segi pria masalah seperti faktor koitus, ejakulasi, pekerjaan dan faktor lain dapat menyebabkan kejadian infertilitas. Faktor usia dan gaya hidup juga tak luput dari penyebab infertilitas sekunder.Konsultasi kepada dokter kandungan sangatlah penting bagi pasangan yang belum mendapatkan anak setelahminimal satu tahun menikah. Kata kunci : ejakulasi, infertilitas, ovulasi, seksual